MANAGEMENT OF ACUTE RESPIRATORY DISTRESS SYNDROME IN A CHILD WITH ADENOVIRUS PNEUMONIA: CASE REPORT AND LITERATURE REVIEW - Oliveira,Felipe Rezende Caino de (2020)
ABSTRACT Objective: To report the case of a child who developed acute respiratory distress syndrome (ARDS) from a pulmonary infection by adenovirus. Case description: A female patient aged 2 years and 6 months, weighting 10,295 grams developed fever, productive cough and vomiting, later on progressing to ARDS despite initial therapy in accordance with the institutional protocol for ARDS treatment. The child evolved to refractory hypoxemia and hypercapnia, requiring high parameters of mechanical pulmonary ventilation and use of vasoactive agents. In the treatment escalation, the patient received steroids, inhaled nitric oxide (iNO), was submitted to the prone position, started oscillatory high-frequency ventilation (HFOV) and extracorporeal membrane oxygenation (ECMO) was indicated due to severe refractory hypoxemia. During this time, the patient’s clinical response was favorable to HFOV, improving oxygenation index and hypercapnia, allowing the reduction of vasoactive medications and mechanical ventilation parameters, and then the indication of ECMO was suspended. The patient was discharged after 26 days of hospital stay without respiratory or neurological sequelae. Comments: Adenovirus infections occur mainly in infants and children under 5 years of age and represent 2 to 5% of respiratory diseases among pediatric patients. Although most children with adenovirus develop a mild upper respiratory tract disease, more severe cases can occur. ARDS is a serious pulmonary inflammatory process with alveolar damage and hypoxemic respiratory failure; Adenovirus pneumonia in children may manifest as severe pulmonary morbidity and respiratory failure that may require prolonged mechanical ventilation. Exclusive pulmonary recruitment and HFOV are advantageous therapeutic options.